Modelagem do equilíbrio térmico de frangos de corte: um estudo da geração e transferência de calor - Nascimento, Sheila Tavares [UNESP] (2015)
Due to global warming and the imminent increase of animal production in tropical areas, the study about thermal equilibrium of the animals becomes essential, once that thermal stress influences directly their productivity. Poultry has a major importance in the Brazilian agricultural scene, so there is a great importance to the development of techniques applicable to birds' husbandry conditions, to predict their condition of thermal comfort. Based on these information, the main objective was to propose a model of the thermal equilibrium of broiler chickens. The specific objectives were: to study the physiological variables (rectal temperature, skin temperature, feather temperature, exhaled air temperature and foot temperature) of broiler chickens during the rearing period in different environmental conditions; to study the sensible heat flow of broilers chickens in the rearing period in different environmental conditions; to develop and to validate a mathematical model to the prediction of body temperatures of broiler chickens; to determine the amount of radiation to broiler chicks to the maintenance of body temperature; to propose a methodology to measure the metabolic heat production and respiratory functions of broiler chickens (tidal volume, respiratory rate, ventilation) in the rearing period; to apply physiological and respiratory variables measured during the rearing period to sustain a mathematical model to study the heat transference in broiler chickens. The study was performed with the data collection in several trials and flocks of animals, and the birds were exposed to different environmental conditions and seasons. The body temperatures of broiler chickens were studied during the rearing period in July and December. These variables were influenced by the age (live weight) and by environmental variables (P<0.05). The sensible heat flow in the body covered by the feathers and in the foot was also different in accordance ...